APPLICATION OF QAULAN BALIGHA COMMUNICATION PRINCIPLES BY USTADZ FELIX SIAUW ON THE YOUTUBE CHANNEL - Nurul Hidayat; Irma Yusriani Simamora (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
ABSTRACT In the current digital era, social media platforms such as YouTube have become a very effective medium for disseminating information and da'wah. This research analyzes the application of the principles of qaulan baligha communication by Ustadz Felix Siauw in content published on his YouTube channel. Qaulan Baligha is one of the principles of communication in Islam which has four signs: words that touch the heart, contain wisdom, fluency in speaking and the choice of words that are easy to understand which emphasizes clarity and accuracy. The aim of this research is to determine the application of Qaulan Baligha communication principles carried out by Ustadz Felix Siauw and to provide knowledge that Islamic communication principles can be applied efficiently and the importance of clear and appropriate communication in conveying da'wah messages through digital media. This research uses a qualitative approach, descriptive content analysis method. Data collection was carried out by means of non-interactive participant observation, coding and documentation. Then the data was analyzed using data reduction techniques, data presentation and drawing conclusions for the entire research carried out. The subjects in this research were preaching videos uploaded on Ustadz Felix Siauw's YouTube channel with the titles